Morfologia maxilar em indivíduos com síndrome de apnéia obstrutiva do sono - Ruiz, Mylena Teixeira (2008)
The objective of this study was to verify the presence of maxillary morphologic parameters on the Obstructive Sleep Apnea Syndrome (OSA) The sample was consisted on maxilla dental models of 23 individuals (11 males and 12 females) with the polyssonographic diagnosis of mild SAOS, 34 individuals (17 males and 17 females) with moderate SAOS and 17 individuals with severe SAOS (14 males and 3 females) Measures of maxilla dental models of 50 young Brazilians were used for the control group, both males and females and with normal occlusion and without any indication OSA The results found show that the maxillary morphologic parameters evaluated didn’t show the association with the apnea/hypopnea index (AHI) but minor transversal dimensions of the maxilla mainly at the level of the molars associated to the increase of the dessaturation of oxyhemoglobin (minSaO2) The individuals with OSA also presented maxilla transversal dimensions narrower and more height on the palate at the region of pre-molars and molars when compared to the control group.